GOOD CORPORATE GOVERNANCE MODERATES THE EFFECT OF ENVIRONMENTAL PERFORMANCE AND SOCIAL PERFORMANCE ON FINANCIAL PERFORMANCE - Nicholas Renaldo; Suhardjo Suhardjo; Suyono Suyono; Andi Andi; Kristy Veronica; Robert David (International Conference on Business Management and Accounting, 2022)
This study aims to determine the effect of environmental performance and social performance on financial performance with good corporate governance as a moderating variable. This research was conducted on service companies listed on the Indonesian Stock Exchange (IDX) during 2017-2021. This type of research is quantitative research with a sampling technique using a purposive sampling method. The type of data used in this study is secondary data obtained from annual reports and sustainability reports obtained indirectly through intermediaries or internet media. Data analysis in this study used descriptive analysis, classical assumption testing, multiple linear regression analysis, and moderate regression analysis (MRA). The results showed that: environmental performance affects financial performance, social performance affects financial performance, Good Corporate Governance strengthens the influence of environmental performance on financial performance, and Good Corporate Governance weakens the impact of social performance on financial performance.